Association of Hearing Loss with Physical, Social, and Mental Activity Engagement - Goman, Adele M.; Gao, Tess; Betz, Joshua; Reed, Nicholas S.; Deal, Jennifer A.; Lin, Frank R.; for the ACHIEVE-P Study Group (Seminars in Hearing, 2021)
This article aims to evaluate a hearing loss intervention versus an aging education intervention on activity engagement in the Aging and Cognitive Health Evaluation in Elders pilot (ACHIEVE-P). Forty adults (70–84 years) with hearing loss recruited from the Atherosclerosis Risk in Communities Study and de novo participated. Participants were randomized 1:1 to a best practices hearing intervention or a successful aging intervention. Hearing was measured with pure-tone audiometry. The Community Healthy Activities Model Program for Seniors questionnaire measured self-reported time engaging in activities at baseline and 6-month follow-up. At baseline, greater hearing loss was associated with reduced time per week on mental activities (−3.0 hours per 10 dB of hearing loss, 95% confidence interval: −5.8, −0.2). Mental activity engagement increased (mean: +1.3 hours, SD = 6.6) for the hearing intervention group but decreased (mean: −1.1 hours, SD = 4.8) for the aging education group (Cohen's d: 0.41). Hearing loss may be associated with reduced engagement in mental activities. Whether hearing loss treatment impacts activity will be studied in the full-scale ACHIEVE trial.
Keywords: hearing loss; activity engagement; mental; social; physical